Yield of sugarcane submitted to nitrogen fertilization and water depths by subsurface drip irrigation - Cunha,Fernando N. (2016)
ABSTRACT Water is limiting for growth and essential for photosynthesis. Crop yield depends on the available amount of this resource and on the efficiency of its use by the plant. This study aimed to evaluate the vegetative growth and the gross yield of sugar and ethanol from sugarcane along cane-plant and ratoon cane cultivation, under different irrigation depths for water replenishment, with and without nitrogen (N) application by subsurface drip irrigation. The experimental design was randomized blocks, analyzed in a split-plot scheme, with four replicates, in which the plots were represented by the interaction: irrigation depths (0, 25, 50, 75 and 100% water replenishment of the field capacity), with and without N fertigation, and subplots were represented by 9 evaluation periods (90, 120, 150, 180, 210, 240, 270, 300 and 330 days after planting/days after the first cutting for ratoon cane). The gross yields of sugar and alcohol for water replenishments below 93 and 97%, respectively, are higher in sugarcane of first year than in sugarcane of second year. Fertigation provided greater vegetative growth of ratoon cane.